Pengaruh Kepemilikan Manajerial dan Free Cash Flow terhadap Manajemen Laba - Benarda Benarda (EkoPreneur, 2020)
This study aims to examine the effect of managerial ownership and free cash flow on earnings management in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2016-2019 period. The data used is secondary data by taking data from the company's financial statements which can be downloaded on the website www.idx.co.id. The sampling method used is purposive sampling using 15 samples from 54 company populations. The data analysis technique used is multiple linear regression analysis using a software program, namely SPSS 25. The results show that managerial ownership has a significant effect on earnings management. The results of the study simultaneously show that managerial ownership and free cash flow have a significant effect on earnings management.Keywords : Managerial Ownership, free cash flow, Earnings Management.